FAMILY SUPPORT AS A FACTOR RELATED TO THE SELF EFFICACY OF POST STROKE PATIENTS - Fuji Istiana (The Shine Cahaya Dunia D-III Keperawatan, 2023)
Background: Self-Efficacy is one of the psychological problems experienced by post-stroke patients. One of the factors related to post-stroke patient self-efficacy is family support. Stroke sufferers will experience various disorders. So for some of the impacts caused by stroke, stroke sufferers need help from family, friends and health workers.Method: The type of research used is a non-experimental study with cross sectional research methods. The research respondents were post-stroke patients at the Sultan Agung Islamic Hospital Semarang who met the inclusion criteria, totaling 62 respondents who were selected using a non-probability sampling technique in the form of purposive sampling. Data collection was carried out using a family support questionnaire. Data analysis to determine the relationship between demographic characteristics including age, gender, education, and marital status, as well as predictor variables of family support and post-stroke patient self-efficacy.Results: Research shows that the majority of respondents were >55 years old (59.7%), male (51.6%), had low education (54.8%), were married or had a partner (61.3%) , good family support (61.3%), and good self-efficacy (58.7%). The results of statistical tests using the Chi square test show that the p value is <0.05 (0.02). This shows that there is a relationship between family support and post-stroke patient self-efficacyConclusion: Family support is one of the factors related to post-stroke patient self-efficacy. Key words: Family support, self-efficacy, post-stroke.